Symposium 12: Blended Learning and its Evaluation: Symposium Introduction - Motschnig-Pitrik, Renate (Proceedings of the International Conference on Networked Learning, 2004)
We will have to value the work of community building and make sure that participants have access to the resources necessary to learn what they need to learn in order to take actions and make decisions that fully engage their own knowledgeability. (Wenger, 1998, p. 10). When I have been able to transform a group into a community of learners, then the excitement has been almost beyond belief. To free curiosity; to permit individuals to go charging off in new directions dictated by their own interests; to unleash the sense of inquiry; to open everything to questioning and exploration; to recognize that everything is in process of change – here is an experience I can never forget. (The Carl Rogers Reader; Kirschenbaum & Henderson, 2002, p. 304). Significant learning […] is learning that makes a difference – in the individual’s behavior, in the course of action he chooses for the future, in his attitudes and in his personality. (Rogers, 1961, p. 280)